REKONTEKSTUALISASI KOMUNIKASI PARIWISATA DALAM REKONSTRUKSI INTEGRASI NASIONAL - Misnan Misnan; Iswahyu Prana Wukir (Jurnal Ilmu Komunikasi PROGRESSIO, 2021)
The purpose of this research is to know the role of recontextualization of tourism communication in the reconstruction of national integration. Through the constructivist paradigm with descriptive methods, the recontextualization of tourism communication is an effort for sustainable social change with a pattern of cultural tourism. On the other hand, the reconstruction of national integration is a horizontal effort in assembling the dimensions of differences, whether regional differences, residences, ethnic differences, religious differences, cultural differences and other differences. The conclusion obtained is that through tourism communication, which has the core management of meaning of sustainable and cultural tourism, a national